PEMBERDAYAAN MASYARAKAT MELALUI REVITALISASI POJOK BACA CERIA SEBAGAI RUANG SOSIAL-EDUKATIF INOVATIF - Sri, Wage; Desi Aryani; Muslim Ansori; Wahidin; Feby Virzinia Dwiftra (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Abstract Community empowerment is an essential effort to improve human resource quality and foster community independence. Limited access to literacy resources and educational interaction spaces remains a significant challenge in many regions, including the location of this program. This activity aims to revitalize Pojok Baca Ceria as an innovative social-educational space to enhance reading habits, broaden information access, and encourage active community participation. The method applied a participatory approach involving the provision of reading facilities, literacy training, community mentoring, and optimizing the use of social spaces. The results indicate a significant improvement in reading interest, digital literacy skills, and community involvement in managing the reading corner independently. The program’s implication demonstrates that integrating education, literacy, and social spaces can create a sustainable empowerment ecosystem. In conclusion, the revitalization of the reading corner through innovation and collaboration effectively strengthens community literacy levels and fosters more productive social interactions. Keywords: community empowerment, reading corner, literacy, social space